Pengaruh Lingkungan Kerja dan Disiplin Kerja Terhadap Kinerja Karyawan PT Arkstarindo Artha Makmur di Bekasi - Daniel; Siti Ruhana Dara (UNIVERSITAS KALBIS, 2022)
This study aims to determine the effect of work environment and work discipline on the performance of employees of PT Arkstarindo Artha Makmur in Bekasi. This research is a quantitative research. Samples were taken as many as 60 respondents in the location of the West Java branch in the city of Bekasi. The sampling method used is non-probability sampling with a quota sampling type, with a total of 60 respondents. The measuring instrument used is a questionnaire using a Likert scale via google from. The data in this study uses the SPSS 20 program. From the results of the analysis of the hypothesis that the work environment has no significant effect on employee performance, work discipline has a significant effect on employee performance, work environment and work discipline simultaneously affect the performance of PT Arkstarindo Artha Makmur employees in Bekasi.